Nazi ideology and ethics - Bialas, Wolfgang, 1954-; Fritze, Lothar (Cambridge Scholars Publishing, 2014)
This volume documents the still-rare encounter of moral-philosophical, historiographic and medical-ethical research on National Socialism, and looks at the ethical aspects of the National Socialist ideology, as well as at the moral convictions of National Socialist perpetrators, some of whom acted as ""perpetrators with a good conscience"". It furthermore discusses questions such as the content and rationale of Nazi race ethics, the ""euthanasia"" killings and the Nazi ethics of racial warfare an ...